Analisis Usahatani Budidaya Pakcoy Secara Hidroponik NFT (Nutrient Film Technique) Pada Lahan Sempit - Safitri, Lilian; Pakpahan, Sophia Angelina; Lapihu, Yunindah Lestari (Jurnal Pertanian Terpadu, 2024)
Agriculture using hydroponic system is widely used by the community, especially in narrow land such as in residential areas, one of which is the NFT (Nutrient Film Technique) system. Pakcoy is one type of vegetables that are in demand by the public. Pakcoy can be cultivated with NFT hydroponic system with the aim to produce maximum production because of the guaranteed amount of nutrients from the nutrients provided. This research has been conducted during March to April 2021 in a narrow area of residential area with a land area of 500 m2. This research was conducted by collecting primary data (from farmers) and secondary data (from literature and relevant research results). The results showed that Pakcoy cultivation farming using NFT hydroponic system is feasible to be applied with a B/C value of > ratio of 1 which is 6.20. The cost required in the manufacture of installation is Rp. 24,130,000 and can be utilized for 4 years with the total cost required of Rp. 967,604/harvest, the profit obtained is Rp. 660,000/ 45 days.